Meta-analysis of Studies Investigating Association between FTO Gene Polymorphisms and Breast Cancer - Gholamalizadeh, Maryam; Doaei, Saeid; Sanjari Moghadam, Ali; Movafagh, Abolfazel; Mousavi Jarrahi, Seyedeh Zahra; Mosavi Jarrahi, Alireza (Asian Pacific Journal of Cancer Biology, 2019)
Back Objectives: The aim of this study is to pool the result of studies on the association between FTO gene polymorphisms and breast cancer (BC). Material and Methods: We searched PubMed, Embase, Science Direct, Scopus, web of science, and Cochran to identify studies investigating the associations between the rs1477196 and rs9939609 polymorphisms and BC risk. We pooled adjusted odds ratios (ORs) as overall. ORs were estimated using a random effects model. Results: In total, 16 articles were included in the final analysis. Considering the dominant model of inheritance, there was an inverse association between the rs1477196 polymorphism and BC (OR 0.76 [0.64- 0.91]). There was not observable heterogeneity (I2: 0.0%, P=.867), but with a small study effect (b=1.19, P=.03) in this analysis. Moreover, there was not any association between the rs9939609 polymorphism and BC (OR 0.98 [0.79- 1.2]). There was not observable heterogeneity (I2: 23.1%, P=.27) and small study effect (b=-3.817, P=.303) in this analysis. Conclusions: The carriers of rs1477196 polymorphism of FTO are at lower risk for BC. Carriers of Rs9939609 polymorphism had no association with Breast cancer risk.